2014
DOI: 10.4084/mjhid.2014.028
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Inhibitors and Pregnancy

Abstract: The management of patients with chronic myeloid leukemia (CML) during pregnancy has become recently a matter of continuous debate. The introduction of the Tyrosine Kinase Inhibitors (TKIs) in clinical practice has dramatically changed the prognosis of CML patients; in fact, patients diagnosed in chronic phase can reasonably expect many years of excellent disease control and good quality of life, as well as a normal life expectancy, including the necessity to address issues relating to fertility and pregnancy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 41 publications
5
91
0
8
Order By: Relevance
“…Zhou et al [14] recently reported on the successful pregnancy outcome in the partner of a man on treatment with nilotinib at a dose of 800 mg daily for 31.5 months at the time of conception. The second case was reported by Abruzzese et al [18] in which a 33-year-old male conceived on nilotinib after 40 days of exposure, resulting in the delivery of a healthy offspring.…”
Section: Male Patientsmentioning
confidence: 96%
See 1 more Smart Citation
“…Zhou et al [14] recently reported on the successful pregnancy outcome in the partner of a man on treatment with nilotinib at a dose of 800 mg daily for 31.5 months at the time of conception. The second case was reported by Abruzzese et al [18] in which a 33-year-old male conceived on nilotinib after 40 days of exposure, resulting in the delivery of a healthy offspring.…”
Section: Male Patientsmentioning
confidence: 96%
“…More recently, Abruzzese et al [18] summarized the outcome of 167 of a total of 210 pregnancies in women exposed to imatinib. These women were all exposed to imatinib during period of organogenesis (>5 weeks gestation).…”
Section: Female Patientsmentioning
confidence: 99%
“…For women with CML, there is strong evidence to suggest that TKIs during pregnancy confer a small increased risk of spontaneous abortions and a significantly increased risk of congenital malformations including bony and renal deformities, and others. [62][63][64] Hence, it is recommended that TKIs be discontinued for pregnancy. Women who become pregnant and discontinue imatinib without achieving a durable major molecular response (MMR) experience poor outcomes, with loss of responsiveness to imatinib upon resumption of drug.…”
Section: Special Consideration: CMLmentioning
confidence: 99%
“…The role of TKI in pregnancy has been riddled with controversies due to potential fetal malformations [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Imatinib, a newer category D drug is a tyrosine kinase inhibitor (TKI) which can prolong CP of CML thereby improving the quality of life, short of curative option of stem cell transplantation. TKI in pregnancy have shown fetal abnormalities recently despite contradicting anecdotal reports of favourable outcomes in the past [6][7][8]. Though there is enough information on the use of TKI in pregnant females with CML, surprisingly there is little information on the effects of CML per se on the pregnancy and on the complications encountered both in baby/mother secondary to CML.…”
Section: Introductionmentioning
confidence: 99%